A convenient synthesis of 4-arylidene-2-phenyl-5(4H)-oxazolones under solvent-assisted grinding. Issue 29 (20th July 2016) - Pattarawarapan, Mookda; Jaita, Subin; Phakhodee, Wong
Graphical abstract: Highlights: The TCT-mediated synthesis of Erlenmeyer azlactones is reported. Condensation of hippuric acid with aromatic aldehydes proceeded rapidly. The products were afforded in high yields without column chromatography. Abstract: A facile and effective approach for the synthesis of 4-arylidene-2-phenyl-5(4 H )-oxazolones has been developed. Under solvent-assisted grinding in the presence of 2, 4, 6-trichloro-1, 3, 5-triazine, catalytic triphenylphosphine, and sodium carbonate, dehydration–condensation of hippuric acid with aromatic aldehydes proceeded rapidly within minutes at room temperature to afford the products in good to excellent yields.